2014
DOI: 10.3758/s13414-014-0818-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sport expertise on representational momentum during timing control

Abstract: Sports involving fast visual perception require players to compensate for delays in neural processing of visual information. Memory for the final position of a moving object is distorted forward along its path of motion (i.e., "representational momentum," RM). This cognitive extrapolation of visual perception might compensate for the neural delay in interacting appropriately with a moving object. The present study examined whether experienced batters cognitively extrapolate the location of a fast-moving object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 58 publications
2
35
3
Order By: Relevance
“…This is in fact the case. The lag in the flash-lag effect varies from about 27 ms to about 90 ms (Arnold et al, 2009;Chakravarthi & VanRullen, 2012;Eagleman & Sejnowski, 2000van de Grind, 2002), but the amount of extrapolation in RM can be several hundred milliseconds (Nakamoto, Mori, Ikudome, Unenaka, & Imanaka (2015).…”
Section: Representational Momentum (Rm)mentioning
confidence: 99%
See 1 more Smart Citation
“…This is in fact the case. The lag in the flash-lag effect varies from about 27 ms to about 90 ms (Arnold et al, 2009;Chakravarthi & VanRullen, 2012;Eagleman & Sejnowski, 2000van de Grind, 2002), but the amount of extrapolation in RM can be several hundred milliseconds (Nakamoto, Mori, Ikudome, Unenaka, & Imanaka (2015).…”
Section: Representational Momentum (Rm)mentioning
confidence: 99%
“…This can be contrasted with the flash-lag effect, where it has been found that active control of the moving stimulus by the participants reduced, rather than enhanced, the extent of the flash-lag effect (Ichikawa & Masakura, 2006), at least when the coupling between mouse movement and stimulus movement had a familiar directional relation (Ichikawa & Masakura, 2010). It is therefore most likely that extrapolation to the present and Extrapolation to the present 31 displacement are different phenomena, and that displacement is a case of extrapolation to guide interceptions (Nakamoto et al, 2015).…”
Section: Representational Momentum (Rm)mentioning
confidence: 99%
“…As in typical PM tasks where a target moves toward a stationary destination, we expected to find, for both Chase and Attract, changes in response times as target speed and occlusion period were varied (e.g., Peterken et al, 1991;Baurès et al, 2010;Bennett et al, 2010a;Zago et al, 2010;Nakamoto et al, 2015). Moreover, here we also sought to determine whether having a continuously visible moving destination biases the estimation of target speed during occlusion.…”
Section: Introductionmentioning
confidence: 96%
“…It has been suggested that performance in PM tasks is influenced by imposed oculomotor strategies (Bennett, Baurès, Hecht, & Benguigui, 2010a;Makin & Poliakoff, 2011), characteristics of target motion such as velocity (Sokolov & Pavlova 2003;Baurès, Oberfeld, & Hecht, 2010;Bennett et al, 2010a;Zago, Iosa, Maffei, & Lacquaniti, 2010;Nakamoto, Mori, Ikudome, Unenaka, & Imanaka, 2015), and the duration of target occlusion before it strikes the line (Peterken, Brown, & Bowman, 1991;Baurès et al, 2010). Other factors known to influence performance during PM tasks include the duration of visible motion (Sokolov & Pavlova, 2003), the target size (Sokolov & Pavlova 2003;Battaglini, Campana, & Casco, 2013), the presence of background texture (De Lucia, Tresilian, & Meyer, 2000;Battaglini, Campana, Camilleri, & Casco, 2014), motion aftereffects (Gilden, Blake, & Hurst, 1995;Battaglini et al, 2014), stimulus-to-background contrast (Battaglini et al, 2013), and the presence of visual distractors (Lyon & Waag, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation